2014
DOI: 10.1177/1098612x14539088
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol toxicity in a cat: case report and literature review of serotonin syndrome

Abstract: The literature relating to the pharmacology of tramadol and tramadol overdose, clinical manifestations of tramadol overdose, and serotonin syndrome in cats, humans and dogs is reviewed. Recommended treatment for tramadol overdose and serotonin syndrome is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 57 publications
(139 reference statements)
1
17
0
Order By: Relevance
“…Recently, symptoms related to serotonin syndrome secondary to tramadol overdose (80 mg/kg administered PO twice) have been reported for the first time in a cat. 147 The serotonin syndrome is induced by pharmacological treatment with serotonergic agents that increase serotonin activity, including selective serotonin reuptake inhibitors, tricyclic antidepressants (amitriptyline), monoamine oxidase inhibitors, lithium, carbamazepine, amphetamine and derivatives, dextromethorphan, tramadol and meperidine; and also by St John’s wort ( Hypericum perforatum ). In people symptoms include cognitive behavioural changes, neuromuscular excitability and autonomic instability.…”
Section: Tramadolmentioning
confidence: 99%
“…Recently, symptoms related to serotonin syndrome secondary to tramadol overdose (80 mg/kg administered PO twice) have been reported for the first time in a cat. 147 The serotonin syndrome is induced by pharmacological treatment with serotonergic agents that increase serotonin activity, including selective serotonin reuptake inhibitors, tricyclic antidepressants (amitriptyline), monoamine oxidase inhibitors, lithium, carbamazepine, amphetamine and derivatives, dextromethorphan, tramadol and meperidine; and also by St John’s wort ( Hypericum perforatum ). In people symptoms include cognitive behavioural changes, neuromuscular excitability and autonomic instability.…”
Section: Tramadolmentioning
confidence: 99%
“…In humans, serotonin syndrome typically has three forms of symptoms, including neuromuscular hyperactivity (tremor, clonus, hyperreflexia, rigidity), autonomic hyperactivity (pyrexia, tachycardia, tachypnea) and altered mental status (agitation, excitement). 8,9 In cats, serotonin syndrome has been reported in conjunction with tramadol and selective serotonin reuptake inhibitor (SSRI) toxicity. 8,10 In cats with SSRI-induced serotonin syndrome clinical signs consisted of sedation, gastrointestinal signs (vomiting, diarrhea, nausea, drooling), central nervous stimulation (vocalization, hyperactivity, hyper-reflexia, agitation, tremors), cardiovascular signs (tachycardia, bradycardia, hypertension) and hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports in human beings have associated trazodone or tramadol use with serotonergic syndrome (Margolese and chouinard 2000, Kitson and Carr 2005, Takeshita and Litzinger 2009). Tramadol toxicity leading to serotonergic syndrome has been reported in a cat (Indrawirawan and McAlees 2014). One study of trazodone in conscious dogs found six of six greyhounds developed a transient tachycardia following intravenous administration of 8 mg/kg trazodone and three of the six developed signs of aggression.…”
Section: Discussionmentioning
confidence: 99%